The cubature smooth variable structure filter estimation strategy applied to a quadrotor controller - Al-Shabi M; Gadsden SA; Wilkerson SA (SPIE, the international society for optics and photonics, 2015)
Unmanned aerial systems (UAS) are becoming increasingly popular in industry, military, and social environments. An UAS that provides good operating performance and robustness to disturbances is often quite expensive and prohibitive to the general public. To improve UAS performance without affecting the overall cost, an estimation strategy can be implemented on the internal controller. The use of an estimation strategy or filter reduces the number of required sensors and power requirement, and improves the controller performance. UAS devices are highly nonlinear, and implementation of filters can be quite challenging. This paper presents the implementation of the relatively new cubature smooth variable structure filter (CSVSF) on a quadrotor controller. The results are compared with other state and parameter estimation strategies.
Keywords: 40 Engineering; 4006 Communications Engineering; 4009 Electronics, Sensors and Digital Hardware; 51 Physical Sciences; 5102 Atomic, Molecular and Optical Physics